KARAKTERISTIK KOMPOSISI KIMIA RUMPUT LAUT MERAH (RHODOPHYCEA) Eucheuma spinosum YANG DIBUDIDAYAKAN DARI PERAIRAN NUSA PENIDA, TAKALAR, DAN SUMENEP - Andarini Diharmi; Dedi Fardiaz; Nuri Andarwulan; ndang Sri Heruwati (Fakultas Perikanan dan Kelautan, Universitas Riau, 2011)
he objective of research was to get the chemical composition of red algal(E. spinosum) from different coastal of water that have the potensial as a sourceof carrageenan. The analysis was conducted to analyze the chemical content ofthe algal (E. spinosum) of three coastal water were moisture content, ash content,protein content, fat content, carbohydrate content and dietary fiber content. Theresults of analysis chemical composition of red algal from different waters hadshowed that content of moisture content 19.55-21.27% , ash content 18.55-18.95%, protein content 4.85-5.59% content, fat content of 0.06-0.1% andcarbohydrate content 53.44-55.52 % while the total dietary fiber content of redalgal (E. spinosum) was 12.78-15;92%. The chemical composition of red algal E.spinosum of three coastal water no real effect unless total dietary fiber contentwas significantly diffrence between the coastal water.